LEGAL ASPECTS OF PP NO 29 OF 2020 CONCERNING INCOME TAX FACILITIES IN THE FRAMEWORK OF HANDLING CORONA VIRUS DISEASE - Agustina Ekra Flamella; Fitika Andraini (Sekolah Pascasarjana Universitas Swadaya Gunung Jati, 2023)
The Legal Aspects of PP No 29 of 2020 Concerning Income Tax Facilities in the Context of Handling Corona Virus Disease (Covid-19) and the impact after the enactment of PP No 29 of 2020 Concerning Income Tax Facilities in the Contex of Handling Corona Virus Disease (Covid-19) for UMKM. This study uses an empirical juridical approach which is a type of legal research conducted by looking at the real conditions of the community environment with the intent and purpose of finding the facts and date needed. The conclusions from this study are (1) The understanding of UMKM actors who still do not understand the contents of PP No 29 of 2020 article (5) to article (6) which states that UMKM actors do not pay taxes but only report their business income to the Web DJP and will be paid by the government which will be accumulated annually. (2) Knowing the impact after the enactment of PP No 29 of 2020, namely UMKM players, especially Semarang Candisari, Semarang City, have made good use of this regulation because IT problems have developed, many UMKM are better acquainted with IT, especially small business, the majority of sellers are elderly and parent. (3) The researcher suggests for all UMKM actors, especially in the Candisari Semarang area, to contribute more to the state througt paying taxes because currently it is made easier by the Government.